Comparison of performance United Kingdom and Malaysia initial public offerings: 2002 - 2006 / Hamdan Mohd Tahir - Mohd Tahir, Hamdan (2007)
This study focus on the long term performance of initial public offerings in Malaysia and United Kingdom for 5 years or 60 periods from 2002-2006. This paper will analyze on 284 IPOs companies that listed in 60 periods of London Stock Exchange and 321 Initial Public Offerings (IPOs) companies that listed in Bursa Malaysia Stock Exchange. London Stock Exchange and Bursa Malaysia Composite Index were used as a benchmark in evaluating share price performance. The objective of this study is to determine the long term performance of IPOs. This is in order to find out whether the United Kingdom and Malaysian IPOs are under performed or over performed in the market long run. To accomplish this task, improved methods for tests of long-run abnormal stock returns introduced which is Buy-and-Hold Abnormal Return by Lyon, Barber and Tsai (1999) has been used to determine the long run performance of IPOs. This study also used t-statistics skewness-adjusted to see the significant of the IPOs. The result show that the performance of returns on all IPOs companies has no significant to the returns on the market for each period either in United Kingdom or Malaysia. So, I conclude that all IPOs companies do not under performed the market and its comparable to the market benchmark.